Correlation of HbF, HbA2, and HbS in sickle cell disease and its prevalence in Nigerian patients: A case series of 2 patients (Indian Journal of Case Reports, 2021)
Sickle cell disease (SCD) is the most common inherited disorder of hemoglobin worldwide. In Nigeria, the prevalence of SCD is 20–30/1000 live births. The burden of the disease has reached a level where it contributes 9–16% of the under-five mortality in many West African countries. This case series evaluated the chromatographic patterns and red blood cell indices of sickle cell homozygous patients. Red cell indices, blood film, sickle solubility test, and chromatographic patterns using Bio-Rad HPLC D10 were evaluated for both patients. Both the patients were Nigerian and HPLC showed HbS window 81.7 and 81.6% and increased HbF, that is, 7.5 and 8.8%. HbA2 was normal in both the cases, that is, 2.2 and 2.6%. Our data suggest that homozygous sickle cell disease is very common among the Nigerian population with an increase in HbF along with HbS and HbA2 is normal.